2015
DOI: 10.1080/00343404.2015.1053446
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital Externalities: Effects for Low-Educated Workers and Low-Skilled Jobs

Abstract: Investments in human capital are essential themes in many policy programs. Besides the direct private returns of education, there is evidence of positive human capital externalities at the level of regions and firms. Our results show that both production and consumption externalities have positive effects on wages. Production externalities are transmitted at the level of firms and not at the regional level. For workers in low skilled jobs, consumption externalities dominate production externalities.Workers on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…The firm effects are robust in both models and help explain underqualification of the low educated. This finding is in line with studies looking into interactions between high-educated and low-educated workers in explaining personal differences in salary; they also found that the firm level is more important in general (Broersma et al, 2010;Canton, 2009).…”
Section: Firm Characteristicssupporting
confidence: 90%
See 2 more Smart Citations
“…The firm effects are robust in both models and help explain underqualification of the low educated. This finding is in line with studies looking into interactions between high-educated and low-educated workers in explaining personal differences in salary; they also found that the firm level is more important in general (Broersma et al, 2010;Canton, 2009).…”
Section: Firm Characteristicssupporting
confidence: 90%
“…However, the interaction between high-educated and low-educated workers can also be explained from a more positive point of view. The presence of highly educated workers is often related to all kinds of positive spillover effects in the region (eg, Rodríguez-Pose and Tselios, 2010) and for the firm (Broersma et al, 2010;Canton, 2009). Low-educated workers can benefit from a higher abundance of better jobs and consumption effects.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of highly skilled, and highly educated workers to unemployment is expected to be negative. This implies that highly skilled labour and those with high education attainments find it easier to get jobs as chances of employment improve with education (Becker, 1964;Broersma et al, 2013;Güçlü, 2017). In this study, this variable is defined as the shares of 'illiterate', 'below intermediate', 'intermediate', 'above intermediate', 'university level and above' to the working age population in the region, respectively.…”
Section: Choice Of Variablesmentioning
confidence: 99%
“…However, greater insight is needed into the underlying mechanism. Broersma et al (2015) show, for example, that, for the Netherlands, an important component of the wage spillover effect results from interactions between individuals within firms rather than interactions between individuals co-located within a region.…”
Section: Human Capital and Regional Economic Developmentmentioning
confidence: 99%